A Place to Belong - Snelling, Lauraine (Minneapolis, Minnesota : Bethany House Publishers, 2013)
Desiring a home, Cassie Lockwood has promised herself to a rancher already living on the land she inherited in the Black Hills of South Dakota, but her heart really belongs to his brother, Ransom Engstrom.
Keywords: Ranch life -- Fiction; Brothers -- Fiction; Black Hills (S.D. and Wyo.) -- Fiction; Christian fiction; Love stories; Western stories